Undergraduate student success factors: The role of OCBI and OCBO / Shaiful Annuar Khalid, Ahmad Redzuan Abdul Rahman and Mahmod Othman - Khalid, Shaiful Annuar; Abdul Rahman, Ahmad Redzuan; Othman, Mahmod (Universiti Teknologi MARA, Perlis, 2006)
The authors' main aim in this study was to identify whether lecturers' OCBI and OCBO influence undergraduate students' academic performance. The authors measured academic performance by students' cumulative grade point average. Student age and gender were tested as moderators. Analysis was conducted on a survey data of 162 students in one of the local public institutions of higher learning. By employing the social exchange theory, the results revealed that OCBI was significantly related to students' academic achievement. In addition, OCBO positively predicted students' academic achievement among female students. Interpretations of results, implication and future research are discussed.